La formación académica y su incidencia en el desempeño de las secretarias ejecutivas de las Junta Parroquial de Pimocha Cantón Babahoyo, Provincia los Ríos. - Calderón Avilés, Reyna (2016)
The aptitude of the professional performance of each person is detailed in the professional field where he works and all this is related to the type of academic training and has acquired, new skills and personal development are also the new skills and development Personnel that are necessary to provide a quality service to the beneficiaries. The main objective of this research is to determine the relationship between the work performance of the secretary of the Parish Council of Pimocha, Babahoyo province Los Ríos. For this reason a good management or management must be supported by administrative assistants, who efficiently manage their functions, that guarantes confidence, seriousness, good treatment, knowledge, skills and abilities in human interrelationships. In addition to knowing how to comply and enforce the policies, rules and procedures of the company or institution, adequately handle computer technology. In the modern world, it is necessary for the board to have a secretary who is not just a receptionist, but an assistant who can contribute to the broad meaning of the role; And the Parish Board secretary can not be the exception, that is why a decision has been made in a research process to see if some way can be supported to ensure that academic training is of better quality. What most stand out in the executive secretary we have that they are irreplaceable collaborators of the boss, is who complies or transmits the orders, registers and classifies any document, resolves and has different situations registers and classifies any document, resolves and attends diverse situations.